Invention of a novel photodynamic therapy for tumors using a photosensitizing PI3K inhibitor. Issue 3 (6th April 2016) - Hayashida, Yushi; Ikeda, Yuka; Sawada, Koichi; Kawai, Katsuhisa; Kato, Takuma; Kakehi, Yoshiyuki; Araki, Nobukazu
Abstract : XL147 (SAR245408, pilaralisib), an ATP‐competitive pan‐class I phosphoinositide 3‐kinase (PI3K) inhibitor, is a promising new anticancer drug. We examined the effect of the PI3K inhibitor on PC3 prostate cancer cells under a fluorescence microscope and found that XL147‐treated cancer cells are rapidly injured by blue wavelength (430 nm) light irradiation. During the irradiation, the cancer cells treated with 0.2–2 μM XL147 showed cell surface blebbing and cytoplasmic vacuolation and died within 15 min. The extent of cell injury/death was dependent on the dose of XL147 and the light power of the irradiation. These findings suggest that XL147 might act as a photosensitizing reagent in photodynamic therapy (PDT) for cancer. Moreover, the cytotoxic effect of photosensitized XL147 was reduced by pretreatment with other ATP‐competitive PI3K inhibitors such as LY294002, suggesting that the cytotoxic effect of photosensitized XL147 is facilitated by binding to PI3K in cells. In a single‐cell illumination analysis using a fluorescent probe to identify reactive oxygen species (ROS), significantly increased ROS production was observed in the XL147‐treated cells when the cell was illuminated with blue light. Taken together, it is conceivable that XL147, which is preferentially accumulated in cancer cells, could be photosensitized by blue light to produce ROS to kill cancer cells. This study will open up new possibilities for PDT using anticancer drugs. Abstract : What's new? Photodynamic therapy is an alternative cancer treatment modality in which patients are administered a photosensitizing drug that preferentially accumulates in tumor cells. Here, using live‐cell imaging, the authors demonstrate that XL147‐treated PC3 prostate cancer cells are rapidly injured by 430 nm light illumination. New anticancer drug XL147 has previously been developed as a pan‐class I PI3K inhibitor. Marked reactive oxygen species (ROS) production was found in the cytoplasm of XL147‐treated PC3 prostate cancer cells when illuminated, suggesting such XL147 cytotoxicity may be attributed to ROS. This study will potentially open up new possibilities for photodynamic therapy using existing anticancer drugs.